2002
DOI: 10.1143/jpsj.71.1840
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of the Anisotropic Structure of Vortices Interacting with Columnar Defects in High-Temperature Superconductors through the Analysis of Lorentz Images

Abstract: Two types of Fresnel contrasts of superconducting vortices in a Lorentz micrograph, corresponding to pinned and unpinned vortices, were obtained by a newly developed 1 MV field-emission transmission electron microscope on a Bi 2 Sr 2 CaCu 2 O 8þ (Bi-2212) thin specimen containing tilted linear columnar defects introduced by heavy ion irradiation. The main features of the Fresnel contrasts could be consistently interpreted by assuming that the vortices are pinned along the tilted columnar defects and by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…There are lot of studies on the defect structure of high Tc materials such as Bi based superconductors, yttrium based superconductors and the newly discovered MgB 2 superconductors [1][2][3][4][5], but there are very few studies on the defect structure of Ru based magnetosuperconductors [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are lot of studies on the defect structure of high Tc materials such as Bi based superconductors, yttrium based superconductors and the newly discovered MgB 2 superconductors [1][2][3][4][5], but there are very few studies on the defect structure of Ru based magnetosuperconductors [6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the first analysis of the contrast features strongly suggests that anisotropy plays an important role in determining the outcome of transmission electron microscopy experiments. 7,8 Therefore, in order to interpret the experimental results in the most accurate and appropriate way and to properly take into account the influence of anisotropy we have investigated the model of a tilted London vortex in a thin anisotropic slab and, on the other hand, extended the pancake model calculations by increasing the number of layers. The obtained results are presented, discussed, and compared to experimental results taken in a variety of different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The upper limit of nine layers related to the computer performance has been more than doubled by approximating the screening layers above and below the layer containing a pancake vortex with a superconducting continuum. r Recent transmission electron microscopy (TEM) observations of superconducting vortices interacting with columnar defects in high-T c superconductors have been performed [1]. It was shown that the main features of the out-of-focus contrast could be consistently interpreted by assuming that the vortices are pinned along the tilted columnar defects and by using a layered or anisotropic model to calculate the phase shift of the electron wave.…”
mentioning
confidence: 99%
“…Once the solution of the algebraic system for the unknown coefficients of the vector potential in the whole space has been found, the electron optical phase shift is calculated by integrating the vector potential along a straight trajectory suitably chosen in order to take correctly into account the overall geometry of the experimental setup, including a tilt of the specimen with respect to the electron beam [1,2]. The field projected in other directions, useful for displaying its main features, is calculated according the same recipe.…”
mentioning
confidence: 99%
See 1 more Smart Citation